The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Matriarcat, maternité et pouvoir des femmes - Braun, Françoise (Anthropologie et Sociétés, 1987)
Matriarcat, maternité et pouvoir des femmes Le matriarcat remis à l'honneur au début des années 70 est un thème privilégié pour la réflexion théorique féministe en anthropologie. En tant que construction intellectuelle, le concept de matriarcat, développé par les évolutionnistes puis par les féministes, met en évidence le discours naturaliste de ces deux groupes et ses effets sur la conceptualisation des rapports de sexe. La discussion du concept de matriarcat est aussi le prétexte à une réflexion sur la maternité et le pouvoir des femmes.
Keywords: 1900-1999; 1980-1989; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques

Méthodologie féministe et anthropologie: une alliance possible - Dagenais, Huguette (Anthropologie et Sociétés, 1987)
Méthodologie féministe et anthropologie : une alliance possible Après un bref énoncé des principes épistémologiques et éthiques qui sous-tendent la recherche féministe et de la stratégie qui en découle dans la poursuite de projets concrets, l'auteure examine les affinités et apports réciproques entre anthropologie et méthodologie féministe puis souligne les contradictions profondes qui, selon elle, rendent problématique actuellement le développement de la recherche féministe en anthropologie. Elle termine en suggérant quelques pistes à suivre par les anthropologues féministes dans un proche avenir.
Keywords: 1900-1999; 1980-1989; amérique du nord; amériques; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; méthodologie; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques

Fertilité naturelle, reproduction forcée - Tabet, Paola (L'Arraisonnement des femmes: essais en anthropologie des sexes, 1985)
Arraisonner quelqu'un, c’est en vieux français tenter de le persuader, argumenter pour lui faire entendre raison. En termes de marine et de police sanitaire, arraisonner un navire, c'est l'interpeller, interrompre sa route pour le contrôler. Ainsi, c'est de la double face, matérielle et mentale, du contrôle et de la manipulation des femmes que traite ce livre collectif. Par l'analyse de sociétés très diverses, anciennes et modernes, comme par la critique des discours scientifiques, les auteurs — ethnologues, sociologues, linguistes – éclairent avec rigueur et imagination théoriques deux domaines encore peu explorés de la problématique des sexes : 1) L’élaboration sociale (politique) de la sexualité et la manipulation des mécanismes de la reproduction — dont l'exposé dément les explications naturalistes ; 2) Les conditions socio-sexuées de la connaissance, les effets sur la conscience de l’oppression matérielle subie et exercée — dont l'analyse exclut toute explication idéaliste. Si les deux sexes sont socialement construits, ce n'est pas de façon symétrique. Objets de raisonnements réducteurs et réduites dans leur corps et dans leur raison, soumises à persuasion ou raisonnées de force, inspectées, contrôlées dans leur tête et dans leur ventre tel un navire sa cargaison, son état sanitaire, son port d'attache : ainsi sont-elles créées « femmes » dans de multiples sociétés. Ainsi s'exerce l'arraisonnement des femmes.
Section: 251 pages
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; corps; cours; discipline; europe; france; féminisme matérialiste; inégalités; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; soc1016; sociologie; systèmes d'oppressions; thématiques

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences